Indian agriculture and rural development: Strategic issues and reform options - von Braun, Joachim; Gulati, Ashok; Hazell, Peter B. R.; Rosegrant, Mark W.; Ruel, Marie T. (International Food Policy Research Institute, 2005)
In this brief, the authors suggest five areas for action to put rural India on a higher growth trajectory that would cut hunger, malnutrition, and unemployment at a much faster pace than has been the case so far. The five areas for action are interlinked and would best work if pursued in conjunction. The authors emphasize investments with a human face that include and reach out to the rural poor and a reorientation of subsidies toward such investments: 1. India should increase investments in rural infrastructure including transport and information technology that connects villages) and agricultural R&D (leading to improved technologies for farmers). 2. India should reorient its social safety nets to create more employment in rural areas; help strengthen the human resource base through education, nutrition, and empowerment of women; and build physical infrastructure. 3. Water is going to be increasingly scarce. Investing large sums in new mega-irrigation schemes may not be the best course of action, but it is important to complete those in which a lot of money has already been invested. 4. India must liberalize its marketing and trade policies to encourage vertical coordination between farms, firms, and forks (supermarkets); facilitate increased flow of rural credit, especially to smallholders, through, say, nonbanking financial intermediaries; and withdraw any special concessions in support of foodgrain policies. 5. Trade liberalization in agriculture has the potential to bring rich dividends to developing countries, including India. To realize this potential, India must work toward establishing and strengthening a rules-based multilateral trading system through WTO negotiations.